Reconnaissance mission: development of an algorithm for indoor localisation system with collaborative multi-robot - Billah, Md. Masum; Khan, Md. Raisuddin; Ahmed, Mohiuddin; Shafie, Amir Akramin (2012)
An algorithm for undertaking indoor localisation of multi-robot reconnaissance mission through collaboration has been presented in this paper. A set of communication techniques, an algorithm for sharing behavior for positioning of agent robots, and appropriate attitude which is useful for a group of robots to work together, are developed for collaborative reconnaissance. Two hexapod robots equipped with inertial sensors like accelerometer and rate gyro are chosen for multi-robot navigation in indoor environment for their advantages over the traditional wheeled robots. The sharing behavior and coordination of motion are verified experimentally through indoor localization. This localization system is applicable in such places where GPS signal is unavailable to identify the agent location.